SYNERGISTIC EFFECTS OF FUNCTIONAL INTERACTION BETWEEN BIOGROWTH ECONOMY AND GREEN ECONOMY IN THE CONTEXT OF DIGITALIZATION AND ECOLOGIZATION - KRAUS, Nataliia; KRAUS, Kateryna (Journal of European Economy, 2025)
The biogrowth economy and the green economy are integral components of the innovative development of economies and the implementation of energy saving principles. The biogrowth economy advocates for the sustainable use and rational consumption of limited resources, protects biodiversity and the biosphere of human existence, and provides individuals with ecosystem innovation and digital services. The green economy, on the other hand, focuses on reducing environmental risks and ensuring the rational use of available natural resources. This article aims to present a model for the functional interaction between the biogrowth economy and the green economy in the context of digital transformation, viewed through the lens of sustainable, inclusive, and innovative growth. The study employs the following methods: analysis – to review the literature on the economics of biogrowth and identify an effective model of the green economy; synthesis – to study the principles of building an economy in the context of sustainable development and greening; comparison – to identify the socio-economic benefits and effects of the functional interaction between the biogrowth economy and the green economy; and the schematic method – to visualize the model of functional interaction between the biogrowth economy and the green economy in the context of digital transformation. The results of the study reveal the foundational principles of the biogrowth economy and the green economy and clarify the essence of their ecological core. The socio-economic and synergistic effects resulting from their interaction are presented through the prism of greening. The biogrowth economy is described and it is shown that its important components are the reduction of carbon dioxide emissions and the mitigation of greenhouse effects, the observance of inclusiveness, barrier-freeness, social and corporate responsibility, and the compliance with ethical and environmental standards. Finally, the study emphasizes the need to increase the value component of the national eco-economy through the development of ecological franchising and ecological agritourism. The scientific novelty of the study lies in establishing the relationships between the biogrowth economy and the green economy through the lens of environmental initiatives, green innovations, and digital technologies, as well as in considering the model of the functional interaction between the biogrowth economy and the green economy in terms of sustainable, innovative, and inclusive growth. The practical value of the study is that it outlines the synergistic effects arising from the interaction between the biogrowth economy and the green economy, which lead to energy-efficient production and more economical consumption. This can be achieved by providing systematic government incentives for ecological business practices, such as «tax holidays» for green businesses, and reducing the number of taxes and tax amounts payable by businesses that gradually reduce production waste and greenhouse gas emissions and increase the use of renewable energy sources in business processes. The future prospects of the study could include the modeling of the biogrowth economy as a basis for the development of national models of innovative and digital development of the economy. JEL: F15, F29, F43, O13, O33, Q00.